OPTIMALISASI METODOLOGI PEMBELAJARAN AL-QUR`AN DALAM MENINGKATKAN MINAT BACA ANAK SANTRI (Studi Kasus Tk/Tpa Agung Darussalam Palu) - Andi Anirah (ISTIQRA, 2015)
This study aimed to describe deeply the optimization of learning quran methodolgy in increasing children's interesting of reading Qur'an, through the implementation of the method, the parent role in motivating children to learn Qur'an. The study design was a descriptive qualitative. The results of this study show that learning the quran in TPA Agung Darussalam Palu using Iqra 'method. The Iqra method is a method that contains of six volumes (volumes 1-6), with an approach that emphasizes on the ability of reading letters, words, sentences until reading the Qur'an. Application of the Iqra ' method has been running well, but it needs more any other development toward better . The parents giving motivation will give some positive influences to the children to increase their ability of reading Qur'an. The role of parents in motivating their children to learn to read the Qur'an is so major that children have the skills in reading the Qur'an, but the inadequated media can not support the learning Qur'an successfully. Media including Iqra 'books including with the card achievements of students, memorizing cards, tadarrus cards, other media such us projector, laptops, markers, tables, chairs, and whiteboards